Simondon reconsidered : An interview with Nathalie Simondon (Nóema, 2021)
In this paper we propose an interview with Nathalie Simondon, responsible for the edition of Gilbert Simondon’s work, in order to shed a light on the topics of ecology, encyclopedism, transdisciplinarity and humanism in Gilbert Simondon’s philosophical production.
Keywords: ecology; encyclopedism; humanism; transdisciplinarity; mecanology